2022
DOI: 10.1590/1679-78256882
|View full text |Cite
|
Sign up to set email alerts
|

High-hardness polyurea coated steel plates subjected to combined loadings of shock wave and fragments

Abstract: To investigate the effect of polyurea on the protective performance of a steel target plate under the combination of shock wave and fragments, the failure characteristics, damage process and micro mechanism of the polyurea coated steel plates with different coating methods under the combination of explosion shock waves and fragments were analyzed through experiments and numerical simulations. The results showed that single-sided coatings aggravated the damage of target plate when the coating thickness was 2 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The polyurea spray construction process is one of the key attributes of polyurea that makes it widely used in various fields. Due to the fast curing characteristics of sprayed polyurea, the coating section shows a loose and porous cheese-like structural feature after the reaction film formation, which is favorable for absorbing energy under high-speed loads [36]. Controlling the reasonable matching of the viscosity of amines and isocyanates through the design of the polyurea formulation is an important part of optimizing the performance of polyurea spraying.…”
Section: Hard Segmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The polyurea spray construction process is one of the key attributes of polyurea that makes it widely used in various fields. Due to the fast curing characteristics of sprayed polyurea, the coating section shows a loose and porous cheese-like structural feature after the reaction film formation, which is favorable for absorbing energy under high-speed loads [36]. Controlling the reasonable matching of the viscosity of amines and isocyanates through the design of the polyurea formulation is an important part of optimizing the performance of polyurea spraying.…”
Section: Hard Segmentmentioning
confidence: 99%
“…Lyu et al [13] observed by thermogravimetric experiments that the thermal decomposition rate of polyurea reached the maximum at a temperature of 386 • C. At a temperature of 700 • C, the polyurea decomposed into carbon residue and lost its protective properties [13]. By comparing the FTIR spectra of polyurea before and after the explosion, Zhang et al [36] found that the area of the carbonyl stretching region and imino stretching region was decreased. It was shown from the practical explosion data that the hydrogen bonds in polyurea were broken, and the microphase separation was also damaged after subjecting the polyurea to the explosion load.…”
Section: Soft and Hard Segment Rearrangement Crystallization And Hard...mentioning
confidence: 99%
See 3 more Smart Citations